Necesidad de reformar el régimen tributario, y el Código Tributario referente al cierre de los locales comerciales que afecta el derecho al trabajo - Ochoa Torres, Holger Cristian (2016)
The Ecuadorian government has established various forms of taxation, the same should are paid by certain members of society enjoying ability to pay, such as in this case the owners of the premises in this way the tax legal relationship between the Administration and individuals, which generates the same rights and obligations for both parties. Likewise in the development of this project I referred to the billing system which is the main reason for a penalty and there are two kinds of taxpayers who are required to keep accounts and are not required to keep accounts this should be in accordance the annual sales revenue of possess each and included their investment. If we mean to describe the turnover we can say that inside it has all the information address of the taxpayer in writing that the seller delivers to the buyer detailing the goods that sold you, indicating deciphered mind the quantity, nature, price and other conditions of sale. In researching this topic, I found that at present the Internal Revenue Service has come to make closures that harm the trader who has made investment and has also generated economic losses have led to complete its work permanently. The theoretical and field work of this thesis allowed me to get criteria, with clear and precise grounds of both referents Bibliographic, legal and doctrinal, that contributed to the verification of goals, and finding the hypotheses, allowing support the proposed changes to the tax code and internal taxation law in the sense that the job guarantee the owner of a shop as its investment generates work sources it contributes to development of Ecuador. The content of the thesis is an intellectual effort of the applicant in the scientific and methodological level, which deals theoretically and empirically limitation in case of the exercise of constitutional law and free legal work properly and without infringing the right to work is guaranteed in the current Constitution , against these closures closing premises, incompatible activity for the trader , because the right to work enshrined in the current Constitution of the Republic of Ecuador is not respected